EFEKTIVITAS KEPEMIMPINAN DALAM MANAJEMEN PENDIDIKAN ISLAM - Ratu Amalia Hayani; Syafri Yanto; Azwar Rahmat; Agung Cucu Purnawirawan; Aslan, Aslan (Jurnal Ilmiah Edukatif, 2024)
This study highlights the importance of leadership effectiveness in Islamic education management with a focus on the influence of Islamic values and managerial capabilities. It was found that the application of Islamic principles such as honesty, justice and ihsan by leaders can create a positive and supportive learning environment. In addition, good communication skills and the ability to foster strong interpersonal relationships also play an important role in building trust and loyalty among staff and students. Meanwhile, managerial skills in strategic decision-making and resource management are key factors in achieving educational goals. The study underlines that support from various stakeholders also greatly influences leadership effectiveness. Thus, the success of Islamic education management depends on the synergy between the application of Islamic values and reliable managerial competencies and optimising the achievement of the vision and mission of Islamic education institutions. The implication of this research is the need for training and leadership capacity building for leaders of Islamic education institutions to face the challenges and dynamics of education in the modern era.